Kajian Variasi Poliploidi pada Ikan Lele Afrika (Clarias gariepinus) - Rani Dwi Suci Hd Putri; Zuhratul Mardhiyah Amir; Lufri Lufri; Yuni Ahda; Abdul Razak (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to explain the variation of polyploidy in catfish. This research method is literature study and literature review. The results showed that there were several forms of polyploid interpretation that were often performed on Clarias gariepinus. The effects of fish polyploidy will produce fish seeds with several advantages such as fast growth, resistance to disease and high tolerance to the environment. In conclusion, the form of variation that is often done produces tetraploid and triploid catfish. Keywords: Polyploidy, Tetraploid, Triploid